Comparative acid tolerances and inhibitor sensitivities of isolated F-ATPases of oral lactic acid bacteria. - Sturr, M G (1992)
pH activity profiles and inhibitor sensitivities were compared for membrane ATPases isolated from three oral lactic acid bacteria, Lactobacillus casei ATCC 4646, Streptococcus mutans GS-5, and Streptococcus sanguis NCTC 10904, with, respectively, high, moderate, and low levels of acid tolerance. Membranes containing F1F0 ATPases were isolated by means of salt lysis of cells treated with muralytic enzymes. Membrane-free F1F0 complexes were then isolated from membranes by detergent extraction with Triton X-100 or octylglucoside. Finally, F1 complexes free of the proton-conducting F0 sector were obtained by washing membranes with buffers of low ionic strength. The pH activity profiles of the membrane-associated enzymes reflected the general acid tolerances of the organisms from which they were isolated; for example, pH optima were approximately 5.5, 6.0, and 7.0, respectively, for enzymes from L. casei, S. mutans, and S. sanguis. Roughly similar profiles were found for membrane-free F1F0 complexes, which were stabilized by phospholipids against loss of activity during storage. However, profiles for F1 enzymes were distinctly narrower, indicating that association with F0 and possibly other membrane components enhanced tolerance to both acid and alkaline media. All of the enzymes were found to have similar sensitivities to Al-F complexes, but only F1F0 enzymes were highly sensitive to dicyclohexylcarbodiimide. The procedures described for isolation of membrane-free F1F0 forms of the enzymes from oral lactic acid bacteria will be of use in future studies of the characteristics of the enzymes, especially in studies with liposomes.